Influence of the Growing Region, Quality Classification and Harvest Year on the Orac (Oxygen Radical Absorbance Capacity) Index of Chilean Cabernet Sauvignon Red Wines [Influencia de la Región de Cultivo, Tipo de Guarda y el Año de Cosecha en el Índice Orac (Oxygen Radical Absorbance Capacity) de Vinos Tintos Chilenos] - Lissi-Gervaso, E (Pontificia Universidad Catolica de Chile, Facultad de Agronomia e Ingenieria Forestal, 2014)
In the present work, we studied the effect of the growing region (IV, Metropolitan or VI - VII regions), quality classification (“Varietal”, “Reserva”, and “Gran Reserva”) and harvest year (2000-2012) on the total phenolic content and antioxidant capacity of thirty-six Chilean Cabernet Sauvignon red wine samples. The Folin-Ciocalteu (FC) and (Oxygen Radical Absorbance Capacity) ORAC methods, employing fluorescein and pyrogallol red as probes, were applied to establish the properties of the wine samples. The obtained results show a strong dependence at of the three indexes on the grape growing region, with higher values obtained in wines from the IV region. These results can be related to the climatic characteristics of this Region, which include dry weather and large temperature differences (nearly 20 °C) between day and night. © 2014, Pontificia Universidad Catolica de Chile, Facultad de Agronomia e Ingenieria Forestal. All Rights reserved.